An Interlayer with Strong Pb-Cl Bond Delivers Ultraviolet-Filter-Free, Efficient, and Photostable Perovskite Solar Cells - Hang, Pengjie; Xie, Jiangsheng; Li, Ge; Wang, Ying; Fang, Desheng; Yao, Yuxin; Xie, Danyan; Cui, Can; Yan, Keyou; Xu, Jianbin; Yang, Deren; Yu, Xuegong (iScience, 2019)
The inorganic metal oxides (IMOs), including titanium dioxide (TiO2) and tin dioxide (SnO2), inevitably induce decomposition of perovskite under UV illumination owing to their photocatalytic activity, and the use of a UV filter will add extra cost and reduce the effective power output. Here, we first reveal that the weak Pb-I bond in I-based perovskite is prone to breakage under UV photocatalysis, leading to serious degradation of the SnO2/perovskite interface. We introduced a chlorine-rich mixed-halide perovskite interlayer (ClMPI), which possesses an excellent tolerance to photocatalysis owing to the strong Pb-Cl bond, between the SnO2 and I-based perovskite. The ClMPI-based device achieves an enhanced efficiency of up to 21.01% (certified 20.17%). Most importantly, the resultant devices can maintain >94% of their initial performance after 180 h under outdoor solar irradiation, >80% after 500 h under UV irradiation, and 500 h under continuous full spectrum illumination at their maximum power points. [Display omitted] •The intrinsic mechanism of PSCs degradation under UV photocatalysis has been revealed•An interlayer with strong Pb-Cl bond has been prepared through ion-exchange•The UV-filter-free, efficient, and photostable PSCs have been achieved Catalysis; Energy Storage; Energy Materials